Comparison of different methods for determining the size of a focal spot of microfocus X-ray tubes - Salamon, M.; Hanke, R.; Krueger, P.; Sukowski, F.; Uhlmann, N.; Voland, V. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2008)
The EN 12543-5 describes a method for determining the focal spot size of microfocus X-ray tubes up to a minimum spot size of 5 extgreekmm. The wide application of X-ray tubes with even smaller focal spot sizes in computed tomography and radioscopy applications requires the evaluation of existing methods for focal spot sizes below 5 extgreekmm. In addition, new methods and conditions for determining submicron focal spot sizes have to be developed. For the evaluation and extension of the present methods to smaller focal spot sizes, different procedures in comparison with the existing EN 12543-5 were analyzed and applied, and the results are presented.
EAM Import::2019-03-13